Characterization And Origin Of Dropstone In Peninsular Malaysia - Anuar, Mohammad Noor Akmal (2018)
Depositional environment and mechanism of dropstones in Malaysia are still debatable whether they are of glaciomarine or non-glaciomarine in origin. In addition, the source of diamictites in these dropstones is not yet known. Therefore, this study was designed to integrate geological field observations and petrographic investigations on some of the dropstones in Peninsular Malaysia to examine their origin. In addition, characterization of diamictites in these dropstones can shed the light on the nature and composition of unexposed basement rocks in Malaysia.